The Relationship between the principal servant leadership and school productivity at madrasah aliyah in west sumbawa - Ahmad Zulfikar; Akhairuddidn Akhairuddidn (Universitas Negeri Padang, 2022)
Schools can be said to be productive if the output has increased and shows positive developments, schools must not stagnate in a comfort zone with low productivity, among the factors that correlate with the productivity of schools is the leadership factor in this case is serving leadership (servant leadership). The purpose of this study was to examine how big the correlation between the variable or servant leadership principal on the variabel of school productivity. In this study using a quantitative approach with a survey method, the total population was 121 respondents consisting of principals and teachers in 5 units of madrasah aliyah in west Sumbawa district, a sampel of 54 was chosen using the proportional stratified random sampling technique using the formula from Solvin, while the data collection instrument used a questionnaire, and the construct cronbach alpha technique, after that analysis requirements test was carried out with normality and linearity tests, then the data analysis used descriptive statistical methods and the Pearson product moment correlation test with help spss 21.00. The results of this study indicate that the significance value is 0.000 ≤ 0.05 with the Pearson correlation value of 0.643 which mean the degree of relationship is in the category of strong correlation, so it can be concluded that there is significant positive correlation between the variabel of servant leadership principal on school productivity at madrasah aliyah in the district of west Sumbawa.